Oregon Fossils, Second Edition - Orr, Elizabeth L. (Book collections on Project MUSE., 2009)
"This revised and expanded edition of Oregon Fossils includes a record of all known fossils in Oregon going back 400 million years, along with collecting localities by county, age, rock formation, and published source. The book also provides a geologic overview of the state, from ocean beaches to the high desert, from the Blue Mountains to the Siskiyous." "Unique among fossil field guides, Oregon Fossils includes both specimen identification and interesting notes about their discovery, naming, and conservation. The narrative is sprinkled with biographical sketches of paleontologists who have contributed to the state's fossil record, and the text is richly illustrated with photographs, line drawings, charts, and maps. A complete bibliography lists full citations to fossil material. The only single volume that provides Oregon's fossil record and history, Oregon Fossils is a well-written, well-organized guide. It is an excellent reference for classroom and library use, for researchers, and for private collectors and hobbyists."--Jacket.